A Combination of Anatolian Propolis and Curcumin Protects Fibroblasts Against Beclomethasone (Nazal Steroid)-Induced Oxidative Stress by Modulating IL-25, MMP-2, VEGF, and FGF-2 Expressions - Tarik Yagci; Sidika Genc; Riza Dundar; Halil Ibrahim Altiner; Ali Taghizadehghalehjoughi (Pharmaceuticals)
Background: Nasal steroids are commonly prescribed in ear, nose, and throat clinics. It is observed that the use of nasal steroids is increasing due to the prevalence of allergic rhinitis. Because beclomethasone (BCM) toxicity is low, it is highly preferred in allergic rhinitis. The rate of toxicity increases with the increase in the duration and dose of BCM use. However, the protective mechanism of Anatolian propolis (AP) and curcumin (Cur) against BCM toxicity has not been fully explained. Aim: The study evaluates the potential BCM-induced toxicity effect on VEGF, MMP-2, IL-25, and IL-10 parameters after Cur and AP treatment. Materials and Methods: Cell viability, oxidative stress, and gene expression were used for toxicity evaluation. Results: AP 2.5 mg/mL and Cur 16 µg/mL show high viability and antioxidant capacity. BCM increased the levels of IL-25, IL-10, and MMP-2, and a decrease was detected in the expression levels of FGF-2 and VEGF. Conclusions: AP and Cur show effective healing, and AP has been shown to improve inflammation more effectively than Cur. However, the combination of AP and Cur significantly improved the induced toxicity effects.